West Nile Virus Infection in Sheep. (January 2017) - Rimoldi, G.; Mete, A.; Adaska, J. M.; Anderson, M. L.; Symmes, K. P.; Diab, S.
West Nile virus (WNV) infection has been detected in many species of birds and mammals, but scant information is available about the disease in small ruminants. West Nile virus was diagnosed in 6 sheep with neurological signs and encephalitis, in California between 2002 and 2014. All sheep had severe lymphoplasmacytic meningoencephalitis. Lymphoplasmacytic myelitis was also detected in 2 sheep where the spinal cord was examined. Brain tissue was positive for WNV detected by polymerase chain reaction in 6 of 6 sheep and by immunohistochemistry (IHC) in 5 of 6 sheep. Viral antigen was not detected by IHC in extraneural tissues in the 3 sheep examined. West Nile virus RNA was sequenced from 2 of 6 sheep, and each one clusters closely with WNV isolated from mosquito pools from nearby locations at similar times. West Nile virus was the most common cause of viral encephalitis in sheep diagnosed at this laboratory between 2002 and 2014, accounting for 6 of 9 sheep.